(untitled) (Eurasian Research Bulletin, 2025)
This article provides a comprehensive study of the Russian language as a unique phenomenon deeply intertwined with the history, culture, and mentality of the Russian people. The analysis covers the historical development of the language, from Old East Slavic to contemporary trends, the influence of external factors (including Turkic and Western European borrowings), and the specifics of its phonetics, grammar, lexicon, and phraseology. Particular attention is paid to how various aspects of the language reflect Russia’s cultural heritage and its influence on other cultures.